Indirect adaptive controller based on a self-structuring fuzzy system for nonlinear modeling and control - Qi, Ruiyun; Brdys, Mietek A. (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, a unified nonlinear modeling and control scheme is presented. A self-structuring Takagi-Sugeno (T-S) fuzzy model is used to approximate the unknown nonlinear plant based on I/O data collected on-line. Both the structure and the parameters of the T-S fuzzy model are updated by an on-line clustering method and a recursive least squares estimation (RLSE) algorithm. The rules of the fuzzy model can be added, replaced or deleted on-line to allow a more flexible and compact model structure.
Keywords: fuzzy control; self-structuring fuzzy model; on-line modeling; stability